Inovasi Industri Daging Buatan dalam Perspektif Fiqh Syafi’i - Hasibuan, Tarmiji Umar Sainaddin; Muslim, Azis (Jurnal Kajian Islam Interdisipliner, 2022)
Penelitian ini untuk mengetahui bagaimana manfaat daging buatan di dunia industri khususnya makanan dan bagaimana Islam menjawab serta menanggapi munculnya daging buatan sebagai penemuan yang menjadi alternatif baru dari para ilmuan. Penelitian ini menggunakan metode kualitatif deskriptif. Data dikumpulkan dari berbagai buku, jurnal, berita, web dan media sosial. Kesimpulan dari penelitian ini adalah daging buatan memiliki manfaat bagi manusia terutama dalam dunia industri untuk memenuhi pasokan daging konvensional dan Islam menyatakan daging buatan halal jika bersumber dari hewan yang dilakukan proses penyembelihan serta hewan yang dianjurkan oleh Al-Qur’an seperti ikan dan belalang, kemudian Islam juga menghalalkan daging buatan yang berbahan vegan (nabati) seperti kacang-kacangan dan jamur. [This study talks about the Islamic view on the innovation of the artificial meat industry. The purpose of this study is to find out how the benefits of artificial meat in the industrial world, especially food and how Islam answers and responds to the emergence of artificial meat as a discovery that is a new alternative from scientists. This research uses descriptive qualitative method. Data is collected from various books, journals, news, web and social media. The conclusion of this study is that artificial meat has benefits for humans, especially in the industrial world to meet the supply of conventional meat and Islam states that artificial meat is halal if it comes from animals that are carried out by the slaughter process and animals recommended by the Qur'an such as fish and grasshoppers, then Islam also allows artificial meat made from vegan (pland- based) such as beans and mushrooms.]